2020
DOI: 10.1007/s00284-020-01973-w
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Potential of Regulatory Sigma Factor Mutants for Wastewater Purification or Bioreactor Run in High Light

Abstract: It is shown that a freshly inoculated culture of the model cyanobacterium Synechocystis sp. PCC 6803 consumed almost all phosphate and 50% of nitrate within 6 days from the nutrient-rich BG-11 growth medium, indicating potential of cyanobacteria to purify wastewaters. Synechocystis sp. PCC 6803 control strain also collected nutrients efficiently from a landfill leachate wastewater KA2 (5.9-6.9 mM ammonium and 0.073-0.077 mM phosphate). Wastewaters might induce oxidative stress to microalgae, which prompted us … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…The sigB gene is induced in high light (Figure 1), although to a lesser extent than the sigD gene, and similar induction of the RNAP-SigB holoezyme is not seen in high light as is seen for RNAP-SigD [3,16]. Our previous results have shown that high amounts of carotenoids, as well as Flv2, Flv4, and Sll0218 proteins, in ∆sigCDE reduce the production of singlet oxygen and confer resistance of PSII against light-induce damage; simultaneously, reduced contents of glutathione and Flv1/3 proteins led to more pronounced oxidative damage in ∆sigCDE than in the control strain.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…The sigB gene is induced in high light (Figure 1), although to a lesser extent than the sigD gene, and similar induction of the RNAP-SigB holoezyme is not seen in high light as is seen for RNAP-SigD [3,16]. Our previous results have shown that high amounts of carotenoids, as well as Flv2, Flv4, and Sll0218 proteins, in ∆sigCDE reduce the production of singlet oxygen and confer resistance of PSII against light-induce damage; simultaneously, reduced contents of glutathione and Flv1/3 proteins led to more pronounced oxidative damage in ∆sigCDE than in the control strain.…”
Section: Discussionmentioning
confidence: 65%
“…The ∆sigBCE strain remains greener in high light than the other strains because the phycobilins and chlorophyll a are not degraded as much as in the other strains and the carotenoid content remains low. Previous studies have shown that the ∆sigBCE strain is more resistant against chemicallyinduced singlet oxygen and H 2 O 2 stresses than the control strain [3,16]. We have previously shown that the amount of the SigD protein is two times as high in the ∆sigBCE strain as the CS strain [16], suggesting that overproduction of SigD might offer protection against some reactive oxygen species.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation